Dryness and banishment: The expropriation of irrigated water from the peasants of the Quisma Valley (North of Chile), 1912-1924 - Castro Castro, Luis (2006)
During the 19th century, the extraction of guano and saltpeter caused the normal difficulties for human existence in the desert region of Tarapacá to increase to levels never imagined until then, especially in relation to the use of water resources. On the one hand, the need to supply drinking water to a population that was growing rapidly and, on the other, the use of a high volume of aquifers by industrial mining processes that produce sodium nitrate, implied assuming different initiatives to satisfy these requirements.